Developing halal tourism in a rural context: The role of Islamic spiritual capital - Kurniasari, Widita Kurniasari; Zakik, Zakik (al-Uqud : Journal of Islamic Economics, 2023)
This research aims to obtain an in-depth description of implementing the concept of Islamic spiritual capital in the development of halal tourism in a rural context. The approach used in this research is qualitative, i.e., a field research study. The results showed the importance of cultivating Islamic spiritual capital, reflected through good corporate governance and work ethic, i.e., working hard, smart, and sincerely. This work ethic involves the body, brain, and heart. Islamic leadership prioritises the traits of STAF (Siddiq/truthfulness, Tabligh/advocacy, Amanah/trustworthiness, Fathonah/wisdom). The concept of Islamic spiritual capital can achieve shared prosperity (maqashid sharia) in the community, Village-Owned Enterprises and Tourism Awareness Group, which is realised in the form of maintaining religion (hifz din), protecting the soul (hifz nafs), protecting the mind (hifz aql), protecting offspring (hifz nasl) and finally, preservation of assets (hifz maal). This research implies that better halal tourism management will increase people's economic empowerment in rural areas and create tourism facilities for Muslim consumers, which can become a means of recreation and worship.